Primary Prevention of Cancer-Related Lymphedema Using Preventive Lymphatic Surgery: Systematic Review and Meta-analysis - Ciudad, Pedro; Escandón, Joseph M.; Bustos, Valeria P.; Manrique, Oscar J.; Kaciulyte, Juste (Indian Journal of Plastic Surgery, 2022)
Background Several studies have proven prophylactic lymphovenous anastomosis (LVA) performed after lymphadenectomy can potentially reduce the risk of cancer-related lymphedema (CRL) without compromising the oncological treatment. We present a systematic review of the current evidence on the primary prevention of CRL using preventive lymphatic surgery (PLS).Patients and Methods A comprehensive search across PubMed, Cochrane-EBMR, Web of Science, Ovid Medline (R) and in-process, SCOPUS, and ScienceDirect was performed through December 2020. A meta-analysis with a random-effect method was accomplished.Results Twenty-four studies including 1547 patients fulfilled the inclusion criteria. Overall, 830 prophylactic LVA procedures were performed after oncological treatment, of which 61 developed lymphedema.The pooled cumulative rate of upper extremity lymphedema after axillary lymph node dissection (ALND) and PLS was 5.15% (95% CI, 2.9%–7.5%; p < 0.01). The pooled cumulative rate of lower extremity lymphedema after oncological surgical treatment and PLS was 6.66% (95% CI < 1–13.4%, p-value = 0.5). Pooled analysis showed that PLS reduced the incidence of upper and lower limb lymphedema after lymph node dissection by 18.7 per 100 patients treated (risk difference [RD] – 18.7%, 95% CI – 29.5% to – 7.9%; p < 0.001) and by 30.3 per 100 patients treated (RD – 30.3%, 95% CI – 46.5% to – 14%; p < 0.001), respectively, versus no prophylactic lymphatic reconstruction.Conclusions Low-quality studies and a high risk of bias halt the formulating of strong recommendations in favor of PLS, despite preliminary reports theoretically indicating that the inclusion of PLS may significantly decrease the incidence of CRL.
Keywords: “lymphedema” (mesh); “lymphatic vessels” (mesh); “primary prevention” (mesh); “microsurgery” (mesh); “lymph node excision” (mesh)